Continuous Flow Synthesis of [Au(NHC)(Aryl)] (NHC=N‐Heterocyclic Carbene) Complexes. Issue 53 (4th August 2021) - Cauwenbergh, Thibault; Tzouras, Nikolaos V.; Scattolin, Thomas; Bhandary, Subhrajyoti; Simoens, Andreas; Van Hecke, Kristof; Stevens, Christian V.; Nolan, Steven P.
Abstract: The use of weak and inexpensive bases has recently opened promising perspectives towards the simpler and more sustainable synthesis of Au(I)‐aryl complexes with valuable applications in catalysis, medicinal chemistry, and materials science. In recent years, continuous manufacturing has shown to be a reliable partner in establishing sustainable and controlled process scalability. Herein, the first continuous flow synthesis of a range of Au(I)‐aryl starting from widely available boronic acids and various [Au(NHC)Cl] (NHC=N‐heterocyclic carbene) complexes in unprecedentedly short reaction times and high yields is reported. Successful synthesis of previously non‐ or poorly accessible complexes exposed fascinating reactivity patterns. Via a gram‐scale synthesis, convenient process scalability of the developed protocol was showcased. Abstract : The continuous synthesis of a range of gold(I)‐aryl complexes is reported for the first time. The recently showcased weak base route is successfully implemented into an operationally simple and readily scalable continuous flow procedure. The reported protocol allows for high reaction rates and mild reaction conditions, all in favor of more efficient and sustainable access to products which are valuable in catalysis, materials science and medicinal chemistry.